KEMAMPUAN BAKTERI ASAM LAKTAT DALAM MENGHAMBAT Salmonella thypii - Rahmiati Rahmiati; Helen Anjelina Simanjuntak; Toberni S. Situmorang (Mahesa Research Center, 2020)
Lactic acid bacteria are known to have the ability to produce antimicrobial compounds known as bacteriocins. This study aims to determine the ability of lactic acid bacteria to inhibit the growth of Salmonella thypii bacteria. In this study, the lactic acid bacteria used were a collection of the Biology Laboratory of the University of Medan Area. Eight types of lactic acid bacterial isolates were used, including IN01, IN02, SF01, SF02, NN01, NN02 SPU01 and SPU04. A confirmation test was carried out on the growth of lactic acid bacteria and Salmonella thypii by visual and microcopic confirmation through differential staining. The results showed that all lactic acid bacteria were a group of gram-positive bacteria in the form of bacilli. The survival of lactic acid bacterial isolates in the environment with variations in pH and salt levels was indicated by the number of colonies that grew after the incubation period. The antagonistic ability of lactic acid bacteria in suppressing pathogenic bacteria was proven by the presence of an inhibition zone in the form of a clean area around the pathogenic colony. It is known that the SPU01 and SF01 bacterial isolates have the highest inhibition zone values, namely 29.79 mm and 28.13 mm.